Comunicação de más notícias e luto de familiares de vítimas da Covid-19: contribuições para enfermagem no contexto dos cuidados paliativos - Lucena, Pablo Leonid Carneiro (2021)
Introduction: COVID-19 is a life-threatening disease, as it has caused infection and death for millions of people. Notably, with each hospitalization and death recorded, there is a social network of family members who are deeply impacted, so it is essential to study characteristics of the communication of bad news and mourning in the victims' relatives. The thesis was divided into three articles: a scopping review and two originals. Objectives: to identify characteristics of communication of bad news and death to family members of victims of COVID-19 in the hospital context in Palliative Care; investigate symptoms of prolonged grief and family members' expectations about the end-of-life care of victims of COVID-19. Method: exploratory, descriptive, cross-sectional study, with a concomitant quantitative qualitative approach. Sample of 135 participants in article 2, and 142 participants in article 3. Online data collection. Analysis from the dimensions of the Spikes protocol and the PG-13 prolonged grief instrument. For quantitative data, descriptive and inferential statistics were used. As for the qualitative data, thematic analysis was applied, with the help of the IRaMuTeQ. CEPE Approval: No. 4,584,374. Results: hospital stay with an average of 16 days, 73% of family members did not have access to visits, 80% received information 1x/day, 31% partially understood the language used by professionals. Up to 24 hours before death, 41% of patients were seriously ill and 22% of family members did not receive information. The death was communicated by telephone or in health services, however 29% claim to have been in receptions or corridors. There were no goodbye opportunities in 85% of cases. Regarding the study of grief, there was a prevalence of 11.4% of prolonged grief disorder (PLT) in family members with grief ≥6 months. In the group with mourning <6 months, the prevalence of TLP symptoms was 29.6%. The following dimensions were evaluated: separation anxiety; cognitive, emotional and behavioral symptoms; social and occupational commitment. It was evident that there is a statistically significant association between Prolonged Grief Disorder and the degree of kinship between the participant and the victim (p < 0.001). As for the participants' expectations regarding end-of-life care, the following themes emerged: permission for a dignified farewell, effective communication and comfort promotion, with an emphasis on pain and suffering relief. Conclusion: the evidence contributes to the advancement of knowledge and nursing practice in the area of palliative care, with emphasis on the communication of bad news, assistance to the bereaved family and end-of-life care. With this, it is possible to propose appropriate interventions to improve the quality of services and reduce negative impacts on the lives of people who will go through similar situations.